Retraction Note: LncRNA LINC00520 aggravates cell proliferation and migration in lung adenocarcinoma via a positive feedback loop - Wen Huang; Xinxing Wang; Fubing Wu; Fanggui Xu (BMC Pulmonary Medicine, 2024)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12890-021-01657-6.